The implementation of internet integration in the teaching of History subject in Putrajaya - Ismail, Zaiton; Zakaria, Halimahton Mahsuri; Aziz, Zahara (Malaysian Educational Technology Association, 2007)
This study was carried out to explore the implementation of internet integration amongst History teachers in three schools in the province of Putrajaya which has comprehensive facilities of ICT. It was a qualitative study which had Grounded Theory as its approach in the process of collecting and analyzing data. The research had been completed within seven months. Data were gathered through interviews, non-participant observations, and documents analysis from six History subject teachers. The collected data were analyzed using the Nvivo version 2.0. The researcher had carried out a continuous comparative method during the data analysis. The study shows that the implementation of internet integration approach in the classroom and computer lab contexts amongst the teachers were low. History teachers also had little exposure in pedagogical knowledge and skills towards integrating internet in their teaching process. Moreover, students’ abilities, time constraint in completing lesson syllabus, teachers’ workload and technical problem of ICT facilities had been identified as elements that influenced the rate of integrating internet in teaching History. Internet was used only as a research tool in the teaching and learning process of History subject. The strategy used by these teachers was to integrate internet in lessons based on online inquiry method and refer to printed website materials given to groups and individual. The History teachers were able to integrate internet in their teaching process at the satisfactory level. They can improve their competencies in integrating internet by continuously using it in their teaching.